Seeking common deviations from South Africa’s tax treaty policy: a comparative analysis identifying trends (regional or otherwise) in treaty practice in bi-lateral tax treaties with countries in Asia, Australasia, North America and South America - Decloedt, Andre (Department of Finance and Tax, 2020)
South Africa experienced an unprecedented growth in its tax treaty network since 1994 as a result of an increase in global trade. In concluding these bi-lateral tax treaties with other countries, South Africa depends primarily on its national model policy during its negotiations with other contracting states. The country’s national tax treaty policy was previously defined in one document, the publication of which has since been discontinued. Apart from Professor C West’s contribution to the global tax community, there is little research information available on the current tax treaty policy of South Africa. It is submitted that the OECD Model and its positions recorded in the commentaries are now widely accepted as the national tax treaty policy of South Africa. The findings of the comparative analysis between the previously documented tax treaty policy and this new widely accepted position of South Africa, suggested that the OECD Model and its recorded positions in the commentaries, subject to a few exceptions, is a fair reflection of South Africa’s national tax treaty policy. It is submitted that South Africa accepted common deviations from its national tax treaty policy when negotiating bi-lateral treaties with countries in the Americas, Asia and Australasia. Previous research failed to provide guidance in this aspect and in an attempt to seek common deviations from South Africa’s national tax treaty policy, a comparative analysis was conducted to identify trends (whether regional or otherwise) in tax treaties with a sample of countries in Asia, Australasia, North America and South America. The findings of this comparative analysis indicated that South Africa successfully applied its national tax treaty policy to a large extend, but does accept common deviations from the policy.